PERENCANAAN PENGANGGARAN DENGAN PERSPEKTIF MULTIKULTURAL DALAM PENINGKATAN PEMBANGUNAN DI KABUPATEN NABIRE PAPUA PEMERINTAH KABUPATEN NABIRE - Lisa Fitria Soraya, Mrs. (Jurnal Ilmiah Administrasi Publik, 2012)
Planning and budgeting is an integrated process, therefore the output of planning is budgeting. In Nabire, planning mechanisms are top down (top-down planning) done by BAPPEDA Nabire is to facilitate the deliberations of development starting from the village (the village) to the districts (districts). Participatory planning is experiencing a lot of obstacles in the field. The results showed that not all elements of society participate in the budgetary planning process is due to various reasons, such as: (a) the preparation time is short, (b) limited resources and information, (c) the attitude of the people themselves that participation is still understood merely a formality. There are several factors which have obstructed the process of planning and budgeting at the District Nabire such as infrastructure, community participation and lack of socialization. While some of the supporting factors, among others, the regulatory framework governing decentralization, direct elections, planning and budgeting. Some of those involved in the policy formulation process is the government planning and budgeting, both the executive and legislative branches, and the community through the development planning discussion forums. Mapping of the multicultural requirement can not be done because the District government not prepare quantitative data and documents related to geography, demographics, poverty, unemployment, physical facilities and infrastructure and the existing infrastructure in the villages as well as documents that contain any tribes scattered in the villages. In the implementation of development, the community must be prepared first so that they can participate at any stage of development. The government should also respect the indigenous peoples with a model of participatory development, and resolving social conflicts should be done on the basis of social principles are adhered to indigenous peoples